Skype como herramienta de aprendizaje y comunicación entre niños de décimo año de educación básica - Tapia Pincay, Maribel Patricia (2019)
The present case study has as an essential point to address the issue related to the use of Skype as a learning and communication tool among children of the tenth year of basic education of the Clemente Baquerizo Educational Unit, and thus demonstrate the importance of using this application in students, to strengthen their learning process. The teaching-learning process has changed substantially today, as the use of technology has contributed greatly to these changes, as educational establishments seek to provide their students with the necessary knowledge for the management of communication tools that favor the didactic process Education becomes increasingly competitive and to achieve a better educational level requires the support of resources that help us in the process of teaching students, such as teaching materials, its use tends to guide and motivate the student in the construction of knowledge, that is, to serve as support in the process of student learning through publications of innovative pedagogical systems using technological tools. Technologies profoundly affect the ways of working. Skype is based on a peer-to-peer (P2P) infrastructure, with a single centralized access server (login server), using two types of nodes: Ordinary nodes: these nodes (computers, mobile devices ...) allow Make and receive calls. Special purpose nodes or super nodes: responsible for helping ordinary nodes connect to other nodes within the Skype network